2015
DOI: 10.1167/iovs.15-17013
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion Cell–Inner Plexiform Layer and Peripapillary Retinal Nerve Fiber Layer Thicknesses in Age-Related Macular Degeneration

Abstract: In eyes with dry AMD, mGCIPL and pRNFL thicknesses were lower than measurements in control eyes, and the average mGCIPL thickness was negatively correlated with the drusen area. However, the pattern of these changes differed from glaucomatous abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
89
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 28 publications
11
89
0
Order By: Relevance
“…Recent studies have indicated the possibility of changes in the internal layer in the early stages of AMD [21] as well as in the GCL and GCC [34,35] . To understand the structures or locations in formations/configurations of interest, we manually evaluated GCL and GCC thickness in subjects with early/intermediate AMD at 12 locations in the horizontal meridian by SD-OCT, and we discovered thickness values close to the ones presented in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have indicated the possibility of changes in the internal layer in the early stages of AMD [21] as well as in the GCL and GCC [34,35] . To understand the structures or locations in formations/configurations of interest, we manually evaluated GCL and GCC thickness in subjects with early/intermediate AMD at 12 locations in the horizontal meridian by SD-OCT, and we discovered thickness values close to the ones presented in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…It would be useful to study the GCC's susceptibility to early/intermediate AMD [35] . This complex may be a good marker for typical disorganized synaptic architectural changes in the early/late stages of AMD [34] . The presence of drusen may cause severe morphological changes in multiple retinal layers due to mechanical pressure [34] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee and Yu [20] found that the GCL–IPL thickness decreased after vitrectomy with ILM peeling. In our study, we found that both the thickness and volume of the ganglion layers decreased in sectors 1, 2, and 5.…”
Section: Discussionmentioning
confidence: 99%